2013
DOI: 10.1111/fpa.12015
|View full text |Cite
|
Sign up to set email alerts
|

Presidential and Media Leadership of Public Opinion on Iraq

Abstract: Much research disputes the president's ability to lead public opinion and shows media to have influenced public opinion concerning the war in Iraq. We argue that although news tone is likely to have affected public support for the war, presidential rhetoric could be influential for two reasons. First, heightened presidential attention to the war increases the public's accessibility to the president's perspective on the war. Second, a survey question that cues the respondent to consider the president explicitly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…While the areas we have explored provide a glimpse into the contexts in which presidents reference their predecessors, analyzing the tone of these references can shed light on the way in which presidents speak about their predecessors. The literature on presidential rhetoric and tone finds that the tone of a president's remarks influences the way the public views the handling of a given event or scenario by a president (see, e.g., Eshbaugh-Soha & Linebarger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the areas we have explored provide a glimpse into the contexts in which presidents reference their predecessors, analyzing the tone of these references can shed light on the way in which presidents speak about their predecessors. The literature on presidential rhetoric and tone finds that the tone of a president's remarks influences the way the public views the handling of a given event or scenario by a president (see, e.g., Eshbaugh-Soha & Linebarger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason to study emotion in mediated discussions of foreign policy is that it can influence the public’s evaluation of the policy (Coleman and Wu, 2010). Examining the US intervention in Iraq in 2003, Eshbaugh-Soha and Linebarger (2014) argue that average citizens pay scarce attention to policy details and simply use cues to form their opinion and decisions. This point echoes other scholars’ views (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Army, as an organization, might not be able to directly influence public opinion on a particular war or major operation, but public support may not be a completely exogenous variable. Several studies have indicated that presidential leadership can influence public perceptions of the war to a limited degree (see, for example, Eshbaugh-Soha andLinebarger, 2014, andTedin, Rottinghaus, andRodgers, 2011). 24 Although the Army cannot control the circumstances that govern its ability to expand, it can at least plan realistically for the conditions it may encounter.…”
Section: Army Capacity Depended Heavily On Conditionsmentioning
confidence: 99%